Mechanisms of lignin degradation and persistent free radical formation under light or thermal exposure - Jianghui Yun; Qiuting Yang; Guorui Liu (Cell Reports Sustainability)
Summary: Lignin is a renewable complex phenolic polymer and is a key structural material in biomass that produces persistent free radicals (PFRs). Significant progress has been made in the understanding of the thermal/photo degradation mechanisms of lignin and its model compounds and the reactive intermediates and products involved in the process in recent years. However, the PFRs produced in this process and their formation mechanisms have received little attention. PFRs can induce the production of reactive oxygen species and affect both the environment and human health. In this work, we summarize the mechanism of lignin degradation under thermal/light exposure, the different types of PFRs produced, the mechanism of reactive oxygen species generation, and their environmental effects. Research on PFRs formed in the process of lignin biomass combustion should be prioritized because of increasing global wildfire events.